The Effect of Thina-middha on Emotional Intelligence of Buddhist Students at School - Gita Gita; Komang Sutawan; Widiyanto Widiyanto; Dedi Kundana; Sutiyono Sutiyono; Mega Julianti; Susanto Susanto (International Journal of Science and Applied Science: Conference Series, 2024)
This study aimed to find Thina-middha on students' emotional intelligence. The problems that occur in students are those who are lazy in doing assignments, procrastinating on assignments at school and home, and students who prefer other activities such as playing games, playing social media, and playing with friends rather than doing assignments. Difficulty dividing time in doing school assignments given by teachers. This study uses a quantitative approach with a survey method. The population in this study was 69. This study was conducted in Junior High Schools with student respondents in the 2023/2024 academic year. The study results showed a significant positive effect between the Thina-middha variable and the emotional intelligence variable of junior high school students in 2024, with a t count of 17.274 and a significance value (0.000 <0.05). The magnitude of the influence of Thina-middha on the emotional intelligence of Buddhist students at Jambi Middle Schools in 2024 can be seen from the R Square, which has a value of 0.817, thus meaning that 81.7% of Thina-middha has a significant influence on student's emotional intelligence, while the remaining 18.3% is influenced by other variables that were not studied.